Emerging photodynamic nanotherapeutics for inducing immunogenic cell death and potentiating cancer immunotherapy. (March 2022) - Zhang, Shenwu; Wang, Jing; Kong, Zhiqiang; Sun, Xinxin; He, Zhonggui; Sun, Bingjun; Luo, Cong; Sun, Jin
Abstract: Immunotherapy has emerged as a promising cancer treatment modality. Despite the rapid progress in cancer immunotherapy, the therapeutic efficiency and clinical translation of immunotherapy are not as satisfactory as expected, especially for the patients with immune-cold tumors. Immunogenic cell death (ICD) represents a particular form of tumor cell death accompanied by the production of tumor-specific antigens, which facilitates the infiltration of effector T cells and potentiates immune response in solid tumors. Thus, ICD contributes to stimulating immune-cold tumors to immune-hot ones. Increasing evidence shows that photodynamic therapy (PDT) is able to effectively induce ICD. Recently, a variety of photodynamic nanotherapeutics have been developed to induce ICD and to potentiate cancer immunotherapy. Herein, this review outlines the recent advances in the field at the intersection of PDT, nanotechnology and ICD, including PDT-induced ICD, PDT-based synergistic induction of ICD, and multimodal immunotherapy in basis of PDT-induced ICD. Finally, the prospects and challenges of these photodynamic nanotherapeutics in ICD induction-based cancer immunotherapy are discussed.